Centrifuge Microscopy to Analyze the Sedimentary Movements of Amyloplasts - Masatsugu Toyota; Norifumi Ikeda; Masao Tasaka; Miyo T. Morita (Bio-Protocol, 2014)
A centrifuge microscope (CMS) functionally consists of a centrifuge producing a centrifugal force (hypergravity condition) and a microscope making an enlarged image of an object. This combination of equipment allows live-cell imaging during centrifugation. We have developed a new CMS (NSK Ltd.) to observe movements of the plant organelles such as amyloplasts, under hypergravity conditions (Toyota et al., 2013). This CMS is distinct from previously designed CMSs in terms of spatio-temporal resolution, ease of use and compactness. Here, we show a quick protocol to prepare a specimen of Arabidopsis inflorescence stem, use the CMS, obtain imaging data and analyze them using a single tracking method.